2019
DOI: 10.17656/jsmc.10233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Critical View of Safety and Infundibular Technique in Laparoscopic Cholecystectomy

Abstract: Background  Laparoscopic cholecystectomy is a one of main surgical procedures that used widely for the treatment of symptomatic gallstones throughout the world. Although laparoscopic cholecystectomy has its own advantages, but bile duct injuries occur more frequently compared to the open cholecystectomy. In this study, critical view of safety (CVS) technique is compared to conventional infundibular technique (IT). Objectives  The aim is to compare critical view of safety with infundibular tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…According to a systematic review and meta-analysis in China, the incidence rate of BDI was 1.12% (16). In a large study in India (17), it was 0.05%, and in a local study (Sulaimani, Kurdistan region, Iraq) (18), it was 0.4%. However, a study by Buddingh et al (4) from the Netherlands showed a significantly lower rate of major BDI after the implementation of routine IOC (1.9 vs. 0%).…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review and meta-analysis in China, the incidence rate of BDI was 1.12% (16). In a large study in India (17), it was 0.05%, and in a local study (Sulaimani, Kurdistan region, Iraq) (18), it was 0.4%. However, a study by Buddingh et al (4) from the Netherlands showed a significantly lower rate of major BDI after the implementation of routine IOC (1.9 vs. 0%).…”
Section: Discussionmentioning
confidence: 99%